Şiir Okumaya Dayalı Türkçe Öğretimi - Demir, Mehmet; Duman, Bilal (Gökkubbe, 2004)
Poetic narrative demonstrates richness of a language more clearly, because poetry as a genre is more effective than other literary genres in terms of explaining emotions. The general purpose of this study is to apply this function of poetry in conveying emotions to the education of Turkish. In this context, at fırst, it deals with reading techniques in poetry and their relevancy in teaching Turkish. In connection with that, various learning strategies are explained. At this point, employing the techniques of poetry reading could be developed as a successful strategy for language teaching. Because this way of education could be more enjoyable it eases the way of teaching and learning. Using the conventions of poetry reading might be an important strategy in teaching Turkish.
Turkish Education Through Poetry Reading
Keywords: Turkish Education Through Poetry Reading; Language; Emotions; Thoughts